2022
DOI: 10.3390/educsci12010050
|View full text |Cite
|
Sign up to set email alerts
|

Smartphones and Learning: An Extension of M-Learning or a Distinct Area of Inquiry

Abstract: The smartphone has become an integral part of the education landscape. While there has been significant smartphone research in education under the guise of m-learning, the unique role of the device suggests that m-learning may not be an appropriate characterization. The purpose of this paper is to review the use of m-learning as a primary descriptor for smartphone- and learning-related research. In support of this goal, the paper reviews the definitions associated with m-learning, smartphones, and related tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…During the COVID-19 pandemic, many universities around the world started to use distance learning platforms, such as M-learning platforms, Blackboard, and others [49]. For example, many universities in Saudi Arabia-such as King Faisal University (KFU)-used the Blackboard and M-learning systems as distance learning tools, as a result of the decision by the Saudi government to close all universities during the COVID-19 pandemic [50]. M-learning systems served as online classrooms in which smartphones could be used by instructors and their students to continue the learning process during the COVID-19 pandemic.…”
Section: Overview Of Mobile Learning As a Distance Learning Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, many universities around the world started to use distance learning platforms, such as M-learning platforms, Blackboard, and others [49]. For example, many universities in Saudi Arabia-such as King Faisal University (KFU)-used the Blackboard and M-learning systems as distance learning tools, as a result of the decision by the Saudi government to close all universities during the COVID-19 pandemic [50]. M-learning systems served as online classrooms in which smartphones could be used by instructors and their students to continue the learning process during the COVID-19 pandemic.…”
Section: Overview Of Mobile Learning As a Distance Learning Toolmentioning
confidence: 99%
“…An M-learning platform is a distance learning platform with many features that support the learning and teaching processes for all education levels in universities. It also contributes to ensuring that lesson plans are carried out and the educational goals of the curriculum are met [50][51][52][53]. An M-learning system features a package of educational tools to support the teaching and learning processes.…”
Section: Overview Of Mobile Learning As a Distance Learning Toolmentioning
confidence: 99%
“…Library and information centres in this generation are set out to create access to information not only through the print medium but also by electronic means to facilitate quick delivery. Other hand Hartley and Andújar (2022) explained the Smartphone is the primary ICT device and has become an integral part of the education landscape. Smartphone and learning-related research produced in the past decade is substantial and of great interest to practitioners and researchers.…”
Section: Introductionmentioning
confidence: 99%
“…While the focus of the Goksu analysis was mobile learning, it reveals the rising importance of the smartphone for learning research. The substantive distinctions between smartphone and mobile learning research necessitate a different review [ 43 ]. A content and bibliometric analysis of augmented reality (AR) and science education research revealed that the preponderance of studies utilized smartphones [ 44 ].…”
Section: Introductionmentioning
confidence: 99%